2017
DOI: 10.1111/nhs.12366
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing parenting efficacy of Asian immigrant, first‐time mothers: A cross‐sectional, correlational survey

Abstract: In this study, we determined the factors influencing parenting efficacy of Asian immigrant, first-time mothers. The research design was a cross-sectional, correlational study. The study included 125 first-time mothers who immigrated and married Korean men, and were living in Korea. Data were collected using translated questionnaires, and analyzed for descriptive statistics, Pearson correlation, and multiple regression analysis. The major finding was that the parenting efficacy of immigrant women was influenced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 28 publications
(34 reference statements)
1
4
0
Order By: Relevance
“…The results of this study showed that in the micro-system level, the higher parenting support by spouse, the higher PSE of working mothers. This result is consistent with previous studies which reported that maternal PSE was significantly influenced by parenting support from spouse [ 13 , 49 ]. During our literature search, we could not find any studies that reported results contradicting the result of this study.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The results of this study showed that in the micro-system level, the higher parenting support by spouse, the higher PSE of working mothers. This result is consistent with previous studies which reported that maternal PSE was significantly influenced by parenting support from spouse [ 13 , 49 ]. During our literature search, we could not find any studies that reported results contradicting the result of this study.…”
Section: Discussionsupporting
confidence: 93%
“…For example, previous studies have reported low overall maternal PSE scores (31.6 ~ 48.1 out of 68) [ 6 , 15 ], with the maternal PSE of working mothers even lower than that of non-working mothers [ 15 ]. In addition, most of these studies were conducted in a piecemeal fashion or did not use a theoretical framework [ 13 , 14 ]. Maternal PSE is a highly complex and multi-faced concept [ 3 , 19 ], so the use of a guiding theory to conceptualize how different variables work together to determine maternal PSE can help increase our understanding [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Possibly, many previous studies highlighted the importance of social support;[1314] while the intervention in the present study was only educational and lacked social support. When providing such interventions, the profits of social support from the family members and spouse should be considered.…”
Section: Discussionmentioning
confidence: 81%
“…According to the transition theory, various transition conditions, such as knowledge and social support from one’s partner, family, and social network, can facilitate or constrain process indicators such as childcare stress as a coping response and outcome indicators such as parenting efficacy in immigrant mothers (Meleis et al, 2000; Roh et al, 2017). Therefore, it is important to develop therapeutic nursing interventions that improve transition conditions, such as childcare knowledge and social support, to reduce childcare stress and enhance parenting efficacy (Meleis et al, 2000; Roh et al, 2017).…”
Section: Introductionmentioning
confidence: 99%